Gamification Effect of Loyalty Program and Its Assessment Using Game Refinement Measure: Case Study on Starbucks - Xin, O.W. (Springer Verlag, 2018)
This paper explores the advantage of loyalty program in the domain of business, while Starbucks is chosen as a case study. It focuses mainly on the point system that provides a certain degree of gamification effect. It considers a game progress model of My Starbucks Rewards to derive a game refinement measure for the assessment of gamification impact. The assessment results indicate that the game element of point system in My Starbucks Rewards shows motivations towards the normal purchasing activities. On the other hand, the point system shows the decreasing of motivation effect towards customersâ purchases over the time. In short, customers are experiencing unsophisticated game experience in a point system which is proved to be a short term incentive that is useful to motivate customers in the early age for a short period of time. Starbucks incorporates both point system and tier system in its loyalty program, targeting to attract new customers as well as retain them for a long time to come. However, the current study only examines the point system of Starbucks. Further research might explore more on structure of loyalty program in restaurant or food industry. Â© 2018, Springer Nature Singapore Pte Ltd.